(3ajV GdbOjQ TQM GdLGeY GdUZjQs - (3GdMOGOj GdbGgQj GdefGhj, Rjf GdOjf, eMeO YHO GdQADa Hf JGL GdYGQajf Hf Ydj Hf Rjf GdYGHOjf, J (B1031 (3g`s ((3GdLGeY GdCehjs)
(3ChdgG (B:s
(3HYO GdHSedI ; aj aj GdeKfGI GdahbjI eY GdWGA GdegedI JWhY GdQLd aj HjJg Cj aj eMdI Scfg HjJ cGf Ch ZjQg (B( (3jRjO Ydi JWhYg (B) (3Cj UdGJg GdJWhYs
(3BNQgG (B:s
(3hYdi gPG GdJbQjQ adG MLI ajg dCMeO aj PgGHg Edi Cf ddeQJgf GdGfJaGY aj ebGHdI GdEfaGb (B( (3N(B) (3aj Gdhba (B( (3J (B: (3Yf CHj gQjQI (B) (3hde jNQLg eSdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 204s
(3eYLe GdeDdajf (B2 / 143s
(3cTa GdXfhf (B1 / 561s
(3GdHOQ GdWGdY (B1/ 357s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs